The appearance of eruptive seborrheic keratoses over linear verrucous epidermal nevus − A report - Poovanur Sadasivam Subramaniam Ranugha; Jayadev B Betkerur; Tarikere Gangadhar Savitha; Shastry Veeranna; Vijaya Basavaraj (Wolters Kluwer Medknow Publications, 2018)
Even though seborrheic keratosis (SK)-like histopathological change has been reported within verrucous epidermal nevi (VEN), SKs developing over epidermal nevi has not been described in the past, hence this report. A 50-year-old female presented with asymptomatic pigmented skin lesions over the right half of the body since birth and the appearance of new itchy raised lesions on these of 3 months duration. On examination, multiple verrucous pigmented papules and plaques, along the Blaschko's lines, were seen involving the right side of the body. Multiple discrete hyperpigmented plaques with a rough surface were seen scattered overlying the linear lesions. There were no similar lesions on the normal skin elsewhere. Investigations for internal malignancy were negative. Biopsy from the linear lesions was suggestive of VEN, while that from the new onset verrucous plaques was consistent with SK. Activating fibroblast growth factor receptor 3 mutations have recently been detected in SKs and VEN. This might explain the colocalization of these in our patient.